The Activation of Hippocampal Microglial Cells and Their Role in the Regulation of Pain - Lei Chen; Li Zeng; Wu Li; Jiang-Shan Li (Journal of Integrative Neuroscience, 2025)
Chronic pain frequently coexists with adverse emotions, including anxiety and depression, significantly affecting patients’ physical and psychological health as well as their quality of life. Changes in hippocampal synaptic architecture, neuronal injury, and diminished neurogenesis significantly contribute to pain-related emotions. Microglia in the hippocampus are implicated in these pathologies. Stimulation or injury leads to microglial activation, which causes pain; prolonged pain causes microglia to continuously release pro-inflammatory factors that induce astrocyte activation, which mediates the apoptosis of hippocampal neurons and abnormal neurogenesis. Concurrently, microglia exhibit aberrant phagocytosis and augmented pruning of hippocampal dendritic spines, which disrupts synaptic plasticity and influences hippocampal long-term potentiation, hence contributing to the emergence of negative emotions. Inflammatory responses in the brain are a prevalent pathological foundation for mood disorders and pain, and the activation or inhibition of microglia M1 polarization can influence pain-related emotions. This review elucidates the significance of hippocampal microglia activation, and their interactions with neurons in the hippocampus and astrocytes, in pain-related emotions.